2x -3 - 6x = 0 -3 = 6x - 2x -3 = 4x x = -3/4
8x2 + 15 + 26x = 8x2 + 26x + 15 = 8x2 + 20x + 6x + 15 = 4x(2x + 5) + 3(2x + 5) = (2x + 5)(4x + 3)
This is how I did it:8x3+4x2+6x+3[8x3+4x2]+[6x+3][(4x2)(2x+1)]+[(3)(2x+1)]....as you can see, this is in the general form of ab+cb, which factored is b(a+c), so:(2x+1)(4x2+3)
-1-2x-4x=19-6x-1 = -19x = 3
2(2x + 3)
2x + 4x + 3 = 6x + 3
6X + 3 = 2X + 19Subtract 3 from each side:6X = 2X +16Subtract 2X:4X = 16Divide by 4X = 4
4x plus 3 plus 2x is equivalent to expression 6x plus 3.
3+6x = 4x+9 6x-4x = 9-3 2x = 6 x = 3
8x2 + 6x - 9 = 8x2 + 12x - 6x - 9 = 4x(2x + 3) - 3(2x + 3) = (2x + 3)(4x - 3)
6x + 3 = 2x + 5 4x = 2 x=1/2
2x+9=6x-3 Therefore 4x=12 -->x=3
4 + 2x
8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)
8x^3 - 12x^2 + 6x - 9 = (8x^3 - 12x^2) + (6x - 9) = 4x^2(2x - 3) + 3(2x - 3) = (4x^2 + 3)(2x - 3)
It is: 11-6x as a simplified expression
(6x^5-4x^2)+(2x^3-3) = 6x^5-4x^2+2x^3-3 The grestest exponent is 5, which is the degree of the above expression.